Pendampingan Dan Pelatihan Manajerial Bagi Pemilik Usaha Perikanan Tradisional Di Desa Pelauw Kecamatan Pulau Haruku Kabupaten Maluku Tengah - Satiah Latuconsina; Julie Th Pelamonia (Politeknik Negeri Ambon, 2017)
This community service activity aims to provide an understanding to business owners regarding the appropriate business management and can guarantee the sustainability of their business and provide understanding to the business owners about the approach of fixing the selling price of fish catch by considering the aspect of business sustainability. Effective mentoring and training activities are conducted for 2 (two) days from 11-12 August 2017 located in Pelauw Village. Activity method is done through tutorial, simulation, and practice. This devotional activity succeeds in making the participants have the ability to manage business activities well so that it enlarges the opportunity to expand the business owned so as to improve the welfare of the community, especially the business actors involved